EFFICACY AND SAFETY OF MEDICAL EXPULSIVE THERAPY WITH ALPHA BLOCKER (TAMSULOSIN) IN DISTAL URETERIC CALCULI (The Research of Medical Science Review, 2025)
Background: The medical condition of ureteric calculi occurs frequently in urological practice since it produces severe pain and major health problems. Alpha blockers and tamsulosin specifically have received extensive research-based investigations by medical experts for use as medical expulsive therapy to limit stone passage invasiveness. The tamsulosin achieves its effects by relaxing ureteric muscles to lower stone resistance while assisting stone removal by the body. The research has examined both the safety aspects and the effectiveness of tamsulosin administration as a treatment to assist stone movement towards its natural exit point from the distal ureter. Through clinical study of patient outcomes, healthcare providers can create the best treatment methods which decreases the need for surgical operations. Objectives: To evaluate how well and safely tamsulosin works for medical expulsive therapy in patients with distal ureteric calculi by analyzing stone passage rates together with expulsion time and adverse effects noted by patients. Study design: A Descriptive study. Place and duration of study: Armed Forces Institute of Urology (AFIU), CMH Rawalpindi from Aug 2023 to Jan 2024 Methods: 202 patients with distal ureteric calculi. Within four weeks of random patient distribution, the research team administered daily doses of tamsulosin 0.4mg together with placebo medicine. The study measured the stone expulsion rate as its main outcome and also investigated the time to expulsion as well as the need for surgical intervention and adverse effects occurrences. The study used mean age and standard deviation assessment and p-values toevaluate differences between groups for statistical significance. The study monitored adverse events continuously during its entire duration to assess safety characteristics of tamsulosin. Results: The mean age of patients amounted to 42.6 ± 9.3 years according to 202 participants. A statistically significant difference was found regarding stone expulsion between the two groups since tamsulosin users experienced the outcome at an 82% rate but placebo users experienced it at 55%. The presence of tamsulosin in the treatment led patients to develop a stone expulsion time of 8.3 ± 3.2 days versus 12.7 ± 4.5 days recorded for placebo group patients (p < 0.05). The administration of tamsulosin reduced the need for surgical treatments because the rate of operations declined from 28% to 12%. The side effects of tamsulosin treatment consisted mostly of mild symptoms such as postural hypotension combined with dizziness that resolved independently in five percent of patients. Conclusion: The pharmaceutical agent tamsulosin proves to be a successful treatment choice, also showing favorable tolerability for people dealing with distal ureteric stones. Stone passage efficiency along with reduced treatment duration as well as lower need for surgical procedures becomes possible through medical treatment. Minor side effects from the drug prove less essential than the positive impacts this treatment has on patients. Tamsulosin functions as a suitable first treatment selection for patients with distal ureteric stones when appropriate for their case.